Analisis Pengaruh Return On Asset (Roa), Bopo, Dan Bi-Rate Terhadap Tingkat Bagi Hasil Produk Funding Dengan Skema Akad Mudharabah Mutlaqah (Studi Pada Bank Syariah Mandiri Periode 2011 - 2018) - Dwi Purwati; Ragil Satria Wicaksana (AGHNIYA : Jurnal Ekonomi Islam, 2020)
The research aims to analyze the effect of Return on Assets (ROA), Operational Costs to Operating Income (BOPO), and BI-Rateter on the level of profit sharing of funding products (savings and deposits) with the mudharabahmuthlaqah contract scheme at PT. Bank SyariahMandiri. The population in this study is PT. Bank SyariahMandiri Period 2011 - 2018. This research is a quantitative research. The analysis was carried out using quarterly secondary data published on the official website of Bank SyariahMandiri for the period 2011 to 2018. The dependent variable of this study is the level of profit sharing of savings and mudharabah deposits. Independent variables include: Return On Assets (ROA), Operational Costs to Operating Income (BOPO) and BI-Rate. The data analysis method used is multiple linear regression analysis, classic assumption test, and hypothesis test (F test and T test), data processing using SPSS 20 software. Based on the test results using SPSS 20 software, ROA, BOPO, and BI-Rate partially positive and significant effect on the level of profit sharing of savings and mudharabahmuthlaqah deposits at Bank SyariahMandiri 2011-2018.